2017
DOI: 10.1055/s-0043-120527
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Improving Adherence to Home-Based Exercise: A Systematic Review

Abstract: Purpose The aim of this review is to list the factors that influence adherence to home-based exercise, and to make recommendations about how to improve adherence. Materials and Methods A literature search was performed in Web of Science Core Collection (Library of ETH Zurich), PubMed and PEDro databases. The following search categories were used: “physiotherapy”, “home-based exercises”, “adherence”, “effectiveness”, “motivation” and “barriers”. Results A total of 38 studies were identified and title and abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 32 publications
2
40
1
2
Order By: Relevance
“…Patients' adherence to home‐based exercise is central to the success of the therapy. Previous studies showed that social support from family members or friends, increased motivation by physical therapy, education, and proper number of exercises are main supporting factors to improve adherence to home‐based exercise . A comprehensive subject group, including physiotherapists, social workers, and family members, is required to evaluate and provide interventions for patients with hip fractures who attend home exercise programmes, which may help to ensure an improvement in patients' adherence to the whole rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' adherence to home‐based exercise is central to the success of the therapy. Previous studies showed that social support from family members or friends, increased motivation by physical therapy, education, and proper number of exercises are main supporting factors to improve adherence to home‐based exercise . A comprehensive subject group, including physiotherapists, social workers, and family members, is required to evaluate and provide interventions for patients with hip fractures who attend home exercise programmes, which may help to ensure an improvement in patients' adherence to the whole rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous literature, adherence was correlated with health self-efficacy and mental and physical HRQL, and we extend these findings to include the explanatory role of treatment adherence. Conceptually, self-efficacy is the self-evaluation of one's ability to carry out contextually-specific behaviors and to access the cognitive-motivational resources necessary for behavior (Bachmann, Oesch, & Bachmann, 2018;Deci & Ryan, 2000). Persons with fibromyalgia who feel more efficacious and masterful in their ability to achieve health-related goals, and who have the self-perceived cognitive resources to do so may, in turn, feel more competent to adhere to treatment, thereby improving HRQL (López-Larrosa, 2013;McGuckin, Prentice, McLaughlin, & Harkin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Supervised programmes provide structure, camaraderie and access to regular health care professional support, yet can be difficult for patients to adhere to due to cost/time of travel and fluctuating health status. Unsupervised, home‐based exercise provides flexibility, limits patient travel and promotes independent lifestyle changes in the patient's own environment . However, despite weekly telephone support and fortnightly observations, the overall adherence rate in the home‐based exercise study conducted by Kruger et al was low (55%).…”
Section: Adherence To Exercisementioning
confidence: 99%